Vibrio fluvialis: an emerging human pathogen - Ramamurthy, Thandavarayan; Chowdhury, Goutam; Pazhani, Gururaja P.; Shinoda, Sumio (Frontiers in Microbiology, 2014)
Vibrio fluvialis is a pathogen commonly found in coastal environs. Considering recent increase in numbers of diarrheal outbreaks and sporadic extraintestinal cases, V. fluvialis has been considered as an emerging pathogen. Though this pathogen can be easily isolated by existing culture methods, its identification is still a challenging problem due to close phenotypic resemblance either with Vibrio cholerae or Aeromonas spp. However, using molecular tools, it is easy to identify V. fluvialis from clinical and different environmental samples. Many putative virulence factors have been reported, but its mechanisms of pathogenesis and survival fitness in the environment are yet to be explored. This chapter covers some of the major discoveries that have been made to understand the importance of V. fluvialis.